Circumcision and Muslim Women’s Identity in Indonesia - Octavia, Lanny (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2014)
In Indonesia, female circumcision is generally perceived as a traditional heritage that must be respected and preserved, as well as a religious injunction that must be followed and implemented. Despite there being a lack of religious arguments, the practice has been deemed as a medium to Islamize a girl and as a strong marker of a girl’s Islamic identity. On the other hand, female circumcision is also associated with local tradition. The practice is intended to purify and preserve a girl’s honor. This reflects a patriarchal ideology that emphasizes the importance of protecting female chastity. This paper unfolds the complicated nature of female circumcision in Indonesia, and examines whether it serves as an expression of religious belief, as a preservation of local tradition or as a violation of human rights.DOI: 10.15408/sdi.v21i3.1217